Aneurysm of the Left Coronary Artery in Postoperative Bland-White-Garland Syndrome. (6th December 2015) - Bravo-Valenzuela, Nathalie Jeanne Magioli; Silva, Guilherme Ricardo Nunes
Abstract : We report a case of anomalous left coronary artery from the pulmonary artery (ALCAPA) or Bland-White-Garland syndrome, present the challenges of performing a differential diagnosis, and discuss the treatment of the syndrome. Although ALCAPA is a rare congenital heart disease, it is one of the most common causes of myocardial ischemia in childhood and presents a diagnostic challenge. A four-year-old girl was referred to a pediatric cardiologist for evaluation of mitral valve regurgitation murmur and heart failure. The transthoracic echocardiogram demonstrated the left coronary artery (LCA) not arising from the aorta, presence of coronary collateral circulation, and moderate mitral valve regurgitation. ALCAPA was confirmed using angiotomography. The LCA was surgically reimplanted into the aorta. After 3 years of postoperative follow-up, the patient developed an LCA aneurysm. Diagnosis of cardiac ischemia in childhood remains a challenge, and careful evaluation of coronary arteries on the echocardiogram is an important tool. In this report, we present a case of ALCAPA with an uncommon postoperative outcome.